Monday Club building invoice, Julia Morgan and J. Jepson, payment 19 - Julia Morgan::::::::: (1934)
Payments to J. Jepson, H.G. Klaucke, Sandercock Transfer Co., Chapek's Hardware, and Pacific Coast Coal Co.